MRI safety practices: Ensuring patient and staff well- being in the magnetic environment - Sami Gharem Alamry7, Sarah Marzouq Alnufaei Alotaibi8, Abdulrahiman Muhammad Alkharashi 9., Basim Sallah Almutairi1, Khaled Mohammed A ALMoadi 2, Fayez majed Alharbi3, Aziz Ahmed Alyami4, Shaima Edrees Alruwaished5, Abdulaziz Saad Alsulaiman 6 (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Developing a magnetic resonance imaging (MR) safety protocol is essential to guaranteeing patient and staff safety during MR imaging. A core safety council and a wider safety committee made up of all-important stakeholders are part of the organizational structure. Together, these groups strive to establish a strong safety policies and procedures, enforce device regulations for entry into the MR setting, build MR safety zones, address intraoperative MR concerns, ensure safe scanning parameters and guarantee appropriate communication among all parties involved in the MR environment.Aim: The purpose of the current review is illustrating and understanding safety instructions and protocols for maintaining a good safety practice and ensure patient and staff well being safety in magnetic environment.Method: A systematic review is maintained from electronic databases in English language and from published papers from 2009 to 2021.Result: 13 articles was selected and reviewed based on inclusion criteria and focus on the various policies of safety practice to ensure patient and staff well-being safety in magnetic environment.Conclusion: The literature that was retrieved indicates that safety guidelines for patient safety and staff well-being in magnetic environment have been established according to the current body of knowledge.